A comparative study of unintentional injuries among schooling left-behind, migrant and residential children in China - Hongwei Hu; Jiamin Gao; Haochen Jiang; Pingnan Xing (BMC, 2018)
Abstract Background Children who suffer from parental migration have been manifested to exhibit physical and mental impairments at higher rates. This current study aims to explore unintentional injury disparity among schooling left-behind children, migrant children and residential children in China, and to examine the risk factors of unintentional injury among the three types of children based on a multi-level system framework. This study will fill the gaps of this topic for China and contribute to the world literature in the context of countries with frequent population migration. Methods Data for 4479 children aged 6-16 of a representative population sample were obtained from a survey conducted in China in 2017. Child's unintentional injury in this survey was measured based on the definition and classification of ICD-10. Descriptive analysis, multivariable logistic regression and zero-inflated negative binomial regression were employed in this study. Results Left-behind children showed higher prevalence of total unintentional injury than migrant and residential children, as well as in 14 specific unintentional injuries. There was a statistical difference between left-behind and residential children's unintentional injuries, but no significant difference was found between migrant and residential children. Results also indicated that both individual and environmental factors constructed as a multi-level system were associated with children's unintentional injuries. Conclusions Family migration may have contributed to the increased unintentional injury risks among children. Left-behind children were more vulnerable to suffer from unintentional injuries than migrant and residential children, and specific attentions should be paid to unique group of children, especially the left-behind children. Given the importance and serious consequences of children's unintentional injuries, the findings may provide implications for necessary intervention.